Monitoring, indicators and community based forest management in the tropics: pretexts or red herrings? - García, C.A.; Lescuyer, G. (Springer, 2008)
Over the last 20 years, transfer of the management of natural resources to local populations has been a major trend in the tropics. Many of these initiatives today incorporate the development of monitoring systems based on Criteria and Indicators (C&I), used to gauge environmental, socio-economic, and institutional consequences over a long period of time. The design of C&I at a local level involves combining scientific expertise with traditional ecological knowledge. There are numerous methods of merging these two branches of knowledge and developing a local monitoring system. The difficulty lies in setting up these local monitoring systems. A review of the literature available demonstrates that the handing over of monitoring systems to local communities has rarely been successful. In almost every case study, when the donor agency initiating the process withdrew, monitoring was either much less intensive or came to a complete stop. Despite this blatant deficiency local monitoring systems constitute an almost compulsory component of any donor-funded program/project dealing with sustainable management of natural resources. In our views, the real implementation of C&I by and for communities can only be achieved if there is a genuine devolution of management power, including responsibilities and benefits, to local stakeholders. Unless they link environmental changes to the communities’ own management decisions, formal participative monitoring systems will continue to fail.